A Cross-national Examination of Political Trust in Adolescence: The Effects of Adolescents' Educational Expectations and Country's Democratic Governance. (June 2019) - Kim, Hyungryeol
Can the predisposition to attain education affect the trust adolescents have in their country's political institutions? Utilizing data from 2009 International Civic and Citizenship Education Study (ICCS), this study examines the effect of educational expectations on adolescents' political trust. My multilevel analyses produced nuanced results. While educational expectations have statistically significant effects on adolescents' political trust in most countries, the direction and strength of such effects are conditional upon the country's overall quality of existing democratic governance. Political trust in adolescence may well be a function of one's predispositions to attain education as well as national democratic conditions.